Distance education in the system of factors of adaptability of the social sphere of Ukraine - Verkhovod, Iryna; Oleksenko, Karina; Chernenko, Oleksandr; Semenova, Olena; Mazurenko, Yanina (Interacción y Perspectiva, 2024)
Due to the decreasing accessibility of the educational process under the current restrictions (which, together with COVID and martial law, are continuing for the fourth year), critical processes are taking place that directly affect the decline in the quality of education, which, in turn, does not allow to form the necessary competencies in modern schoolchildren. The purpose of the study is to assess the complex consequences of the spread of distance education in Ukrainian secondary schools regarding the ability of the Ukrainian social sphere in general and the educational sphere in particular to adapt to the conditions and challenges of modern life. We used the methods of analytical grouping, factor analysis of time series, structural-functional analysis and other scientific methods. The study concludes that the current conditions of compromise between accessibility (prevalence) and quality of education in Ukraine imply a shift towards preserving accessibility at the cost of a forced reduction in quality, as well as potential distance. education as a factor in improving its quality is not fully utilized.